Comparison of ATP values on Vegetables Cutting Boards before and after Alcohol Disinfection (Global Journal of Medical Research, 2020)
Sanitary control of cutting boards in the kitchen is important to prevent food poisoning. To preventing secondary and tertiary contamination of food poisoning bacteria, it is necessary to know the hygiene status of cooking utensils. Therefore, in this study, we compared the values after cooking, washing, and spraying 70% alcohol on cutting boards for vegetables using the ATP test and microbiological test. As a result, the ATP value after spraying with alcohol was 100 or less, which was better than that after washing. Microbial test results showed that microorganisms were present on the vegetable cutting board even after spraying with 70% alcohol. Since microorganisms are present even after spraying with alcohol, it is possible that the growth of microorganisms will occur again if the vegetable cutting boardleft in a moist state at room temperature. When using a vegetable cutting board left unattended, it is necessary to wash repeatedly and spray it with alcohol.
Keywords: ATP wiping test; cutting board; hygiene education; double wash